The efficiency of drinking -water-treatment processes in removing of some PAHs compounds from water in Erbil city-Iraq - B. Mohammed, Awaz; M.A.Goran, Siraj; M. Al-Taee, Maysoon (University of Thi-Qar Journal of Science, 2010)
water samples at each treatment step of drinking water treatment plants(DWTPs) in Erbil city were collected to study sixteen PAHs componds listed by USEPA as priority pollutants and determine the efficiency of each process in removal of PAHs .The highest values of(0.313μg/L and 0.233 μg/L)were recorded for Benzo(k)flouranthene in DWTP 1 and 2(Efraz 1,2)during June 2008 in raw water ,while the highest value of 0.174 μg/Lwas recorded for Acenaphtheen and flourene during june 2008 in raw water at Efraz 3.No values were recorded for Low molecular weight PAHs during the study periods at DWTPs in some treatment steps. The lowest values inthe tap water(treated water)which reffered to the efficiency of treatment processes in removing of PAHs from the source water. mean concentration of Total PAHs compounds which ranged between (0.150-1.43 μg/L), (0.081-1.462μg/L) and (0.080-0.0941were recorded at Efraz 1, 2 and 3 during June 2008 and April 2009 in in source water and tap water respectively. the removingpercentage of totl PAHs were (84%,90% and 85%) and (83%,92% and 86%) were recorded at Efraz 1,2,3 during June2008 and April 2009 respectively.The highest values were recorded for 5- ring (BbF,BkF.BaP,DBA)PAHs at Efraz and 2 and 4-ringPAHs(Flur,Py,BaA and chry)at efraz 3